Comparison of Synthesis Techniques for Supported Iron Nanocatalysts - Tasfy, S. H. (Asian Network for Scientific Information, 2011)
Iron-based catalyst is the most common catalyst for Fischer-Tropsch Synthesis (FTS), which is a process to synthesize transportation fuel and chemicals feedstock from the syngas. The effect of synthesis technique, iron loading and catalyst supports on the physicochemical properties of iron-based catalyst was investigated. Impregnation and precipitation methods were used to synthesize the supported iron-based nanocatalysts containing various iron loadings. Silica and alumina silica were used as catalyst supports to modify the catalyst properties in producing well defined phases. The supported iron nanocatalysts were characterized using N2 physical adsorption, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and temperature-programmed reduction (TPR). For the catalysts prepared via impregnation method, the surface area remained at 23m2/g for catalyst containing different iron loading. However, for those prepared via the precipitation method, the surface area of the catalyst increased with increasing iron loading. Precipitation method resulted in highly agglomerated iron nanoparticles. The 6% Fe/SiO2 nanocatalyst prepared via impregnation method resulted in relatively small and uniform dispersion of iron nanoparticles. However, bimodal distribution was observed for the 10 and 15% Fe/SiO2. Similar trend was observed when Al2O3-SiO2 was used as a catalyst support. H2-TPR profiles for Fe/SiO2 nanocatalysts synthesized via impregnation showed two reduction stages while those prepared using precipitation method resulted in three reduction peaks. The TPR peak positions remained the same for various iron loadings.